Analisis Komparasi Sikap Ilmiah Siswa pada Materi Rangkaian Arus Bolak-Balik: Studi Perbandingan Pembelajaran Simulasi Phet dan Metode Ceramah (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
Alternating Current (AC) circuits are abstract concepts that are often difficult for students to grasp, potentially affecting their scientific attitude in learning. This study aims to analyze the differences in scientific attitudes of students taught using PhET simulation media compared to conventional lecture methods. The research method used is comparative descriptive with a Post-test Only Group Design. The sample consisted of 58 grade XII students at SMA 12 Kota Jambi, divided into two classes: Class XII F5 (n=33) as the control class using the lecture method, and Class XII F8 (n=25) as the experimental class using PhET simulation. The data collection instrument used a valid Scientific Attitude Questionnaire (30 items) on a 1-5 Likert scale covering seven indicators: curiosity, respect for data, critical thinking, discovery, open-mindedness, perseverance, and environmental sensitivity. Data analysis results showed that the class using PhET simulation obtained an average scientific attitude score of 4.18 (Very High), outperforming the lecture class score of 3.91 (High). The most significant difference was observed in the Critical Thinking and Respect for Data indicators. This indicates that virtual visualization helps students become more enthusiastic, objective, and critical in processing abstract physical phenomena data.